Matematyka

Autorzy:Wojciech Babiański, Lech Chańko, Dorota Ponczek

Wydawnictwo:Nowa Era

Rok wydania:2015

Uprość wyrażenie 4.67 gwiazdek na podstawie 6 opinii
  1. Liceum
  2. 1 Klasa
  3. Matematyka

`a)\ (x-3)(x+3)+(2+x)(2-x)=(x^2-3^2)+(2^2-x^2)=(x^2-9)+(4-x^2)=`

`\ \ \ =x^2-9+4-x^2=-5`

 

`b)\ (x+3/2)(x-3/2)-(x-1/2)(x+1/2)=(x^2-(3/2)^2)-(x^2-(1/2)^2)=`

`\ \ \ =(x^2-9/4)-(x^2-1/4)=x^2-9/4-x^2+1/4=-8/4=-2`

 

`c)\ (2y-3)^2-(3y-2)(3y+2)=(2y)^2-2*2y*3+3^2-((3y)^2-2^2)=`

`\ \ \ =4y^2-12y+9-(9y^2-4)=4y^2-12y+9-9y^2+4=-5y^2-12y+13`

 

`d)\ (5y+1)(1-5y)-(1+5y)^2=(1+5y)(1-5y)-(1^2+2*1*5y+(5y)^2)=`

`\ \ \ =1^2-(5y)^2-(1+10y+25y^2)=1-25y^2-1-10y-25y^2=-10y-50y^2`

 

`e)\ (2x-y)(2x+y)+(3x+2y)(3x-2y)=((2x)^2-y^2)+((3x)^2-(2y)^2)=`

`\ \ \ =(4x^2-y^2)+(9x^2-4y^2)=4x^2-y^2+9x^2-4y^2=13x^2-5y^2`

 

`f)\ (y+3x)(3x-y)-(x-5y)(x+5y)=(3x+y)(3x-y)-(x^2-(5y)^2)=`

`\ \ \ =(3x)^2-y^2-(x^2-25y^2)=9x^2-y^2-x^2+25y^2=8x^2+24y^2`